(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The paper examines the development of the economies of the Kyrgyz Republic and the EAEU member states in difficult economic conditions. It analyzes the economic processes of the Kyrgyz Republic and the EAEU in 2024. The paper considers the long-term effects within the EAEU. It identifies priority areas for the development of the Kyrgyz Republic and the cooperation of the EAEU member states for the future.